2019
DOI: 10.1016/j.bbamem.2019.183051
|View full text |Cite
|
Sign up to set email alerts
|

G protein-coupled receptors of class A harness the energy of membrane potential to increase their sensitivity and selectivity

Abstract: The human genome contains about 700 genes of G protein-coupled receptors (GPCRs) of class A; these seven-helical membrane proteins are the targets of almost half of all known drugs. In the middle of the helix bundle, crystal structures revealed a highly conserved sodium-binding site, which is connected with the extracellular side by a water-filled tunnel. This binding site contains a sodium ion in GPCRs crystallized in their inactive conformations, but not in GPCRs that were trapped in agonist-bound active con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 92 publications
0
14
0
Order By: Relevance
“…Changes in membrane potential are known to directly modulate activation of GPCRs, especially class A GPCRs (50,54,55). Although the mechanisms by which membrane potential modulates GPCRs are not fully understood, recent studies have shown that allosteric effects of Na + ion on class A GPCRs modulate GPCR activation and GPCR-mediated signaling (54)(55)(56). Binding of voltage-driven translocated Na + to the highly conserved aspartic acid residue in transmembrane domain 2 (Asp 2.50 ) in class A GPCRs, combined with the effects of the Na + -coordinating residues, modulates GPCR agonist binding and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in membrane potential are known to directly modulate activation of GPCRs, especially class A GPCRs (50,54,55). Although the mechanisms by which membrane potential modulates GPCRs are not fully understood, recent studies have shown that allosteric effects of Na + ion on class A GPCRs modulate GPCR activation and GPCR-mediated signaling (54)(55)(56). Binding of voltage-driven translocated Na + to the highly conserved aspartic acid residue in transmembrane domain 2 (Asp 2.50 ) in class A GPCRs, combined with the effects of the Na + -coordinating residues, modulates GPCR agonist binding and activation.…”
Section: Discussionmentioning
confidence: 99%
“…A network of ionizable residues extending through GPCRs is thought to be involved in GPCR signal transduction and may represent an evolutionary link to microbial rhodopsins (9, 12, 24, 49, 50). Our findings therefore suggest that the long-range information pathway we identified may couple the protonation states of the distal conserved Asp 2.50 and Arg 3.50 /Asp 3.49 .…”
Section: Discussionmentioning
confidence: 99%
“…In many cases, ligand binding alone is thought to provide insufficient energy for receptors to transition between inactive and active conformations (3, 9). However, GPCRs are able to harness energy from the membrane potential gradient, potentially through ion and proton transfer (9, 12, 50, 53). Even in the presence of bound antagonists, we observed conformational rearrangements within highly conserved microswitches in the DRY and NPxxY motifs upon protonation of three receptors, which were reminiscent of the transition between inactive and active state crystal structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations